1992
DOI: 10.1128/jb.174.4.1189-1196.1992
|View full text |Cite
|
Sign up to set email alerts
|

The Agrobacterium tumefaciens vir gene transcriptional activator virG is transcriptionally induced by acid pH and other stress stimuli

Abstract: A set of Agrobacterium tumefaciens operons required for pathogenesis is coordinately induced during plant infection by the VirA and VirG proteins. The intracellular concentration of VirG increases in response to acidic media, and this response was proposed to be regulated at the level of transcription at a promoter (P2) that resembles the Escherichia coli heat shock promoters. To test this hypothesis, we first constructed a virG-lacZ transcriptional fusion. A strain containing this fusion had higher levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 65 publications
3
47
0
Order By: Relevance
“…In addition, the affinity of the ChvE protein for sugar acids is increased at low pH, suggesting a link between the sugar and acidity response in A. tumefaciens (Hu et al, 2012). A. tumefaciens utilizes the ChvG/ChvI two-component system to activate the transcription of virG and induces expression of several other bacterial genes (Mantis and Winans, 1992;Chang and Winans, 1996), including genes involved in chemotaxis and motility, several chromosome-encoded virulence genes, succinoglycan biosynthesis genes, and the gene cluster encoding the type VI secretion system (T6SS) (Yuan et al, 2007a;Wu et al, 2008;Wu et al, 2012). Recent studies further identified ExoR as a periplasmic negative regulator acting upstream of the ChvG sensor kinase to repress acid-inducible gene expression (Wu et al, 2012;Heckel et al, 2014) and uncovered a role for the T6SS in interbacterial competition activity during the plant colonization process (Ma et al, 2014).…”
Section: Sensing and Regulation Of Virulence Genes Of A Tumefaciens mentioning
confidence: 99%
“…In addition, the affinity of the ChvE protein for sugar acids is increased at low pH, suggesting a link between the sugar and acidity response in A. tumefaciens (Hu et al, 2012). A. tumefaciens utilizes the ChvG/ChvI two-component system to activate the transcription of virG and induces expression of several other bacterial genes (Mantis and Winans, 1992;Chang and Winans, 1996), including genes involved in chemotaxis and motility, several chromosome-encoded virulence genes, succinoglycan biosynthesis genes, and the gene cluster encoding the type VI secretion system (T6SS) (Yuan et al, 2007a;Wu et al, 2008;Wu et al, 2012). Recent studies further identified ExoR as a periplasmic negative regulator acting upstream of the ChvG sensor kinase to repress acid-inducible gene expression (Wu et al, 2012;Heckel et al, 2014) and uncovered a role for the T6SS in interbacterial competition activity during the plant colonization process (Ma et al, 2014).…”
Section: Sensing and Regulation Of Virulence Genes Of A Tumefaciens mentioning
confidence: 99%
“…Induction of virG by extracellular acidity occurs at a promoter designated P2 and does not require any Ti plasmidencoded protein (23). The virG P1 promoter, in contrast, is activated by phospho-VirG (16,37,43,45) and is also induced by phosphate starvation, probably via a homolog of the E. coli PhoB protein (4,43).…”
mentioning
confidence: 99%
“…Because the induction of virG by acidity and by phosphate starvation does not require the VirG protein, these stimuli have been viewed as necessary to establish a pool of VirG sufficiently large to induce the vir regulon. This pool of VirG, upon phosphorylation, can then more strongly express virG in a positively autoregulated fashion (23).…”
mentioning
confidence: 99%
“…The expression of virulence genes in A. tumefaciens is known to be affected by changes in temperature (23) and pH (32), with 28°C and pH 5.5 being optimal. The thermosensitive nature of virulence expression in A. tumefaciens is due to a reversible inactivation of VirA protein (23).…”
Section: Discussionmentioning
confidence: 99%
“…Once phosphorylated, VirG activates transcription from promoters containing a specific 12-bp sequence called the vir box, which is present in the promoters of all vir genes (25,40). This expression is augmented by the presence of certain monosaccharides (5,43) and an acidic pH (32), which is characteristic of plant wound sites. A periplasmic sugar-binding protein, ChvE, which is highly homologous to glucose-binding protein of Escherichia coli, interacts with the periplasmic portion of the VirA molecule in the presence of certain monosaccharides, including glucose and arabinose (2,15).…”
mentioning
confidence: 99%